Differentiation of Human Adipose-Derived Stem Cells into “Brite” (Brown-in-White) Adipocytes - Pisani, Didier F.; Djedaini, Mansour; Beranger, Guillaume E.; Elabd, Christian; Scheideler, Marcel; Ailhaud, Gerard P.; Amri, Ez-Zoubir (Frontiers in Endocrinology, 2011)
It is well established now that adult humans possess active brown adipose tissue which represents a potential pharmacological target to combat obesity and associated diseases. We had shown previously that human multipotent adipose-derived stem (hMADS) cells are able to differentiate into cells which exhibit the key properties of human white adipocytes, and to convert into functional brown adipocytes upon PPARγ activation that could explain UCP1-expressing cells within islets surrounded by white adipocytes. Herein we further characterize hMADS cells differentiation into brown adipocytes that behave like mouse “brite” adipocytes previously described. We analyzed the expression of gene markers known to be associated with mouse white and brown adipocytes. When shifting from a white to a brown fat cell phenotype, the striking enhancement of uncoupling activity appears mainly due, if not all, to an increase in UCP1 expression whereas induction of UCP2 is weak and UCP3 expression is unchanged. Conversion of white hMADS adipocytes is dependent on PPARγ activation with rosiglitazone as the most potent agonist and is inhibited by a PPARγ antagonist. Furthermore our data show that, in contrast to mouse cellular models, hMADS cells conversion into brown adipocytes is not induced by BMP7 treatment and not modulated by activation of the Hedgehog pathway. No primary or clonal precursor cells of human brown adipocytes have been obtained so far that can be used as a tool to develop therapeutic drugs and to gain further insights into the molecular mechanisms of brown adipogenesis in humans. Thus hMADS cells represent a suitable cell model to delineate the formation and/or the uncoupling capacity of human brown/brite adipocytes that could help to dissipate caloric excess intake among individuals.